PENGARUH GAYA KEPEMIMPINAN, STRES KERJA, DAN KOMITMEN TERHADAP PRODUKTIVITAS KERJA KARYAWAN - AJIE, NABILLA AMMALYA WAHYU; TJAHYANTI, SETIA (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
This research aims to analyze and understand the effect of leadership style, work stress, and commitment on employee work productivity at PT. X. The population in this research consisted of 101 employees, with sampling using a non-probability sampling technique with purposive sampling method involving 98 non-managerial level staff members. The analytical method used in this research is multiple linear regression analysis. The results of this study indicate that there is an influence of leadership style and commitment on employee work productivity of PT. X. However, work stress does not have an influence on employee work productivity at PT. X